The demographic and morbidity characteristics of a population receiving food support in Israel - M. Endeweld; R. Goldsmith; R. Endevelt (BMC, 2018)
Abstract Background Food supply to poor populations is a big challenge, particularly in periods of economic stress and in an era of chronic diseases epidemics. In Israel more than 4000 poor families are currently receiving food support. Many of the food support products given to the family have low nutrient values, therefore not appropriately ensuring food security of the population. The aim of the current study was to examine for the first time the demographic, nutritional and chronic diseases profiles of food support beneficiaries, so as to aid in planning future food support components in Israel. In addition, the study examined associations between levels of food insecurity status and selected morbidities among food support recipients. Methods In 2016, 3000 families (classified as very poor) in 24 municipalities received food support in Israel from the "National Food Security Project" (NFSP), under the guidance of the National Food Security Council. The 400 new families who joined the program in 2016 were requested to complete a questionnaire regarding the demographic and health characteristics of their families. Three hundred sixty-two of them completed the questionnaire for a response rate of 90%. The current study includes these families only. Results The disposable income per capita of the surveyed families was very low - less than NIS 1100 a month ($280). About half the families were working families and 40% of them were in debt. Of the 362 responding families, about 82% of them were food insecure, with more than half severely food-insecure; this, despite receiving food support. About one-third of the families had at least one member with anemia, and a quarter of the families had a member with hyperlipidemia. Hypertension is present in about 22% of the families, diabetes in 17%, and there is a 12% incidence of at least one family member with heart disease. These rates are markedly higher than those in the general population. Higher levels of food insecurity were associated with higher levels of hyperlipidemia, heart disease and hypertension. Discussion and conclusions The nutrition and medical status of the population receiving food support is much worse than in the general population. There is a need to improve the nutritional value of food support; this could include greater emphasis on whole grains, fruits and vegetables. There is also a need for a nationwide education program to focus on healthy nutrition and to subsidize healthy foods. Many health and nutrition promotion models show that in order to effect changes in dietary habits and behaviors related to improving nutrition, there is a need for nutrition education (Kamp et al., J Nutr Educ Behav 42:72-82, 2010).